Los derechos humanos frente al sector minero energético colombiano (2017)
The implementation of the monitoring process in the general code was carried out with the intention of including in our legal system a mechanism of greater accessibility for the citizen of the common; This with the purpose of protecting the claims that they have in money and of which they do not have an executive title with which to make enforceable said obligation. In this article, we will attempt to review the process as such in order to determine its own characteristics, its purpose, the legal nature of the process, the normative aspects and to be able to determine if the process itself is a viable means to guarantee the Minimum amount of money held by a creditor or if it is an ineffective mechanism, for example, for the small trader who has the need to make a debt in money of which he has no judicial title